Estudio de factibilidad para la creación de una empresa transformadora y comercializadora de chontaduro en el distrito de Buenaventura (2013)
The following research aims to conduct a feasibility study to create a processor and marketer of chontaduro Pacific Buenaventura district between the period of 2012 - 2013, to investigate a little more about the fruit of the peach and its production process, and which can be used in various feedstock forms completed. District Consumers have little knowledge about the processes of transformation. The processing and marketing of vacuum packaging peach is a market that has yet to be exploited, as a national natural resource and having the characteristic of being an exotic fruit, has the potential to reach new territories and different types of consumers. Therefore, the researchers are responsible for conducting a thorough analysis on the processing and marketing of locally chontaduro, achieving define marketing strategies internally comprising current market requirements, in order to achieve feasibility study position to new and sustained trading market Buenaventura delivering a good quality product and different presentation to others.